Twentieth century writers, 1950-1990 - Verde, Thomas A. (Thomas Aquinas) 1958- (American profiles, 1996)
This collection of short literary biographies of American writers of the second half of the twentieth century is the continuation of Twentieth Century Writers 1900-1950.